(3TQM GdCOhjI Ydi MQha GdeYLes - (3eSjM Hf Mcje GdeJWHH GdOeTbjs
(3ChdgG (B:s
(3hHYO(B: (3agPG JaSjQ HYV GdCOhjI hGdYbGbjQ GdeHgeI , GdUYHI GdZQjHI , LeYJgG eeG HYO eTghQ HGdcJH GdMceGA s
(3BNQgG (B:s
(3GdOHS GdLHdi , hgh GdeZQjO HMeO Gddg JYGdi hMSf Yhfg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GfXQgG eY JMaI GdCMHGH Qbe (B" 363-365"s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B124 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B_ (3GdQHGW (B(1502(3O(B) s
Keywords: (3GdWHs